The devil and the Dolce vita: Catholic attempts to save Italy's soul, 1948-1974 - Domenico, Roy P. (The Catholic University of America Press, 2021)
The "clerical state" and its critics -- Media and censorship -- Family matters -- The Dolce vita -- "Because this world as we know it is passing away".